MARKETING SOCIAL E AÇÕES DE RESPONSABILIDADE SOCIAL: OS RESULTADOS E O IMPACTO NA EMPRESA E NA SOCIEDADE. - Andrade, Ana Paula de Freitas (2004)
In the past, at the climax of the so-called traditional philanthropy , the donation was a common practice in large companies world. With changes acceleration and social problems intensification, the philanthropy subject and the Social Responsibility practice got new contours and dimensions. The social conscience of the Business community started to awaken when they, themselves realized that the social problems disturbed their business development (population s low income, deficient educational system, violence etc.) This study describes how the companies are dealing with the new institutional paradigm, addresses the mechanisms that are being used on the social actions and how its results are being measured. This work brings as a contribution, the creation of a lager conscience about the Social Responsibility theme through companies investments in that matter, as well as, discusses the citizen concern in promoting a better overall quality of life in society.